일부 지역 치과위생사의 감염관리 인지 및 실천 영향요인 - 정호진; Ho Jin Jeong; 이정화; Jung Hwa Lee (Han'guk Ch'iwisaeng Hakhoe chi, 2015)
Objectives: The purpose of this study is to investigate the cognition and practice of infection control in the dental hygienists. Methods: A self-reported questionnaire was completed by 220 dental hygienists in Busan and Gyeongnam from August 1 to 31, 2014. The questionnaire was adapted from Nam. The questionnaire consisted of four questions of the general characteristics of the subjects, two questions of infection control factors, four questions of clinic environment, 50 questions of awareness of infection control, and 50 questions of infection control practice. Cronbach’s alpha in the awareness of infection control was 0.958 and that in infection control practice was 0.950. Results: The dental hygienists in the large scale hospitals tended to have higher score of cognition and practice of infection control thatn those in the small scale hospitals(p<0.001). Small scale hospitals tended to have lower infection rate than the large scale hospitals. The education for the infection control guideline reduced the infection prevalence rate. Conclusions: In order to reduce the infection prevalence rate, it is necessary to educate the dental hygienists continuously and to provide the infection control guideline to the dental clinics.